Digital Well-being Through the Use of Technology - A Perspective - SUDIP BHATTACHARYA; Sandip Bhattacharya; Vidisha Vallabh; Roy Rillera Marzo; Ruchi Juyal; Ozden Gokdemir (Global Health and Education Projects, Inc., 2023)
"No man is an island unto himself" - John Donne According to the World Health Organization, health is "a state of complete physical, mental and social well-being and not merely the absence of disease and infirmity." Our healthcare industry, public behaviors, and environment have grown exponentially with digital technologies in the era of the 4th industrial revolution. Due to rapid digitalization and easy availability of the internet, we are now online round the clock on our digital devices, leaving behind digital traces/information. These digital footprints serve as an increasingly fruitful data source for social scientists, including those interested in demographic research. The collection and use of digital data (quantitative and qualitative) also present numerous statistical and computational opportunities, further motivating the development of new research approaches to address health issues. In this paper, we have described the concept of digital well-being and proposed how we can use digital information for good health.   Copyright © 2023 Battacharya et al. Published by Global Health and Education Projects, Inc. This is an open-access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0.